CGIAR's Accreditation to UNEA: Strengthening Science for Global Environmental Policy - Edward-Uwadiale, Regina (CGIAR System Organization, 2025)
This article announces that CGIAR—the world’s largest agricultural research partnership—has been formally accredited as an intergovernmental organization (IGO) to the United Nations Environment Assembly (UNEA), granting it official observer status within the United Nations’ principal environmental governance body. The accreditation enables CGIAR to participate directly in UNEA sessions and subsidiary organs, bringing five decades of agricultural science into high-level environmental policy discussions. This strengthened position enhances CGIAR’s capacity to share science-based evidence and recommendations with environment ministers and policymakers, reinforcing the science–policy interface for issues such as climate change, biodiversity loss, land degradation, and sustainable development. Accreditation also enables deeper collaboration with the United Nations Environment Programme (UNEP) and other partners, positioning CGIAR to advance integrated solutions that align agricultural development goals with global environmental targets. The blog highlights how this new status supports contributions to the Rio Conventions on climate, biodiversity, and land restoration, and provides a platform to promote coherent, science-informed policy approaches that link food systems with environmental sustainability